Mass psychogenic illness: an entity poorly studied in Mexico - Miguel Á. Martínez-Medina; Melissa Gastelum-Bernal; Yoseline Cruz-Robles (Permanyer, 2023)
Outbreaks of mass psychogenic illness (MPI) or mass hysteria are common social phenomena worldwide, and Mexico has been no exception.